Implementation of Affective Evaluation on Aqidah Akhlak Learning at MI Adabiyah 2 Palembang Academic Year 2022/2023 - Astuti, Mardiah; Mutyati, Mutyati; Anggilin, Kaliana; Kiftiah, Maryatul; Dita, Etiara Neva (Jurnal Sustainable, 2022)
This study aims to analyze the implementation of affective evaluation in learning Aqidah Akhlak at MI Adabiyah 2 Palembang, focusing on the role of teachers in instilling character values in students. This study uses a qualitative approach with interview techniques as the primary data collection method. The study results show that practical evaluation has been well implemented through using relevant teaching materials, a personal approach to students, and the habit of positive behaviors such as praying, saying greetings, and speaking politely. Teachers play an active role in motivating and guiding students, individually and in groups, to understand and apply the material in daily life. However, challenges are still found in the equitable distribution of the application of character values among students. Some students have shown improvement in behavior, while others need more attention. Therefore, a more systematic and comprehensive strategy is required to ensure that practical evaluation can be applied evenly. This research strengthens the importance of adequate assessment as an integral part of learning Aqidah Akhlak to build the moral character of students with good personalities. The implications of this research provide practical insights for educators and educational institutions in improving the quality of character value-based learning.